Identification of differentially expressed ovarian genes during primary and early secondary oocyte growth in coho salmon, Oncorhynchus kisutch - Iliev Dimitar B; Luckenbach John A; Goetz Frederick W; Swanson Penny (Reproductive Biology and Endocrinology, 2008)
Abstract Background The aim of this study was to identify differentially expressed ovarian genes during primary and early secondary oocyte growth in coho salmon, a semelparous teleost that exhibits synchronous follicle development. Methods Reciprocal suppression subtractive hybridization (SSH) libraries were generated from ovaries with perinucleolus (P) or cortical alveolus (CA) stage follicles and selected genes were assessed with quantitative PCR (qPCR). An assessment of changes in RNA composition during oocyte growth and its relationship to transcript levels was also conducted. Results SSH revealed several differentially expressed genes during early oogenesis, some which will not likely be utilized until 1–3 years later in salmon. Zona pellucida glycoprotein (zp) genes, vitellogenin receptor (vldlr) isoforms, cathepsin B (ctsba), cyclin E (ccne), a DnaJ transcript (dnaja2), and a ferritin subunit (fth3) were significantly elevated at the P stage, while a C-type lectin, retinol dehydrogenase (rdh1), and a coatomer protein subunit (cope) were upregulated at the CA stage. Putative follicle cell transcripts such as anti-Müllerian hormone (amh), lipoprotein lipase (lpl), apolipoprotein E (apoe), gonadal soma-derived growth factor (gsdf) and follicle-stimulating hormone receptor (fshr) also increased significantly at the CA stage. The analysis of RNA composition during oocyte growth showed that the total RNA yield and proportion of messenger RNA relative to non-polyadenylated RNAs declined as oogenesis progressed. This influenced apparent transcript levels depending on the type of RNA template used and normalization method. Conclusion In coho salmon, which exhibit a dramatic change in oocyte size and RNA composition during oogenesis, use of messenger RNA as template and normalization of qPCR data to a housekeeping gene, ef1a, yielded results that best reflected transcript abundance within the ovarian follicle. Synthesis of zp transcripts and proteins involved in yolk incorporation and processing occurred during primary growth, while increased expression of a CA component and genes related to lipid incorporation occurred concomitant with the appearance of CA, but prior to lipid accumulation. Significant increases in transcripts for fshr, gsdf, and amh at the CA stage suggest a role of FSH and TGFβ peptides in previtellogenic oocyte growth and puberty onset in female salmon.